The Role of Educational Management in Promoting Multiculturalism, Democracy, and Human Rights in Indonesia - Fawaid, Mohamad Erihadiana; Yusuf, Ilham Agustian Widia; Puroman, Eman; Setiawati, Fenty (Journal of Educational Management Research, 2025)
This research explores the role of educational management in promoting multiculturalism, democracy, and human rights within Indonesia’s education system. Motivated by the increasing need for character education in Indonesia, the study addresses the erosion of diversity values and mutual respect among students in educational and social settings. It focuses on integrating these educational values into the school curriculum, highlighting the pivotal role of educational management in facilitating this process. Using a qualitative approach, the research employs literature reviews and case studies to analyze the implementation of these principles in schools. The findings indicate that educational management plays a crucial role in integrating multicultural, democratic, and human rights values, fostering respect for diversity, justice, and equality among students. Additionally, continuous teacher training and support are identified as key to effectively implementing these values in the classroom. The implications emphasize the importance of embedding these values into the curriculum and teaching methods, ultimately preparing students to become empathetic, just, and globally-minded individuals. This research contributes to the understanding of how educational management can create a supportive environment that nurtures students’ moral values, ethical behavior, and respect for others, shaping future generations that embrace diversity and contribute to a harmonious society.